2003
DOI: 10.1111/j.1572-0241.2003.07239.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the use of the humanized anti-interleukin-2 receptor antibody daclizumab in active ulcerative colitis

Abstract: The anti-IL-2R antibody daclizumab was safe and well tolerated in acute UC. Patients experienced clinical benefit along with signs of endoscopic improvement, but further controlled trials are needed to determine the therapeutic benefit of this compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…As there was no placebo control group it was not possible to determine if the events were attributable to the administration of basiliximab 29 30. In contrast to the results with basiliximab, although an initial open-label study of 10 patients with refractory UC indicated that daclizumab produced some clinical benefit,31 a larger randomised controlled trial in patients with moderate UC showed that those treated with daclizumab were not more likely to be in remission after 8 weeks of treatment compared with patients given placebo 32. Adverse events were few with daclizumab, with the most common being nausea in patients simultaneously treated with azathioprine31 as well as nasopharyngitis and fever 32…”
Section: Targeting the Adaptive Immune Systemmentioning
confidence: 99%
“…As there was no placebo control group it was not possible to determine if the events were attributable to the administration of basiliximab 29 30. In contrast to the results with basiliximab, although an initial open-label study of 10 patients with refractory UC indicated that daclizumab produced some clinical benefit,31 a larger randomised controlled trial in patients with moderate UC showed that those treated with daclizumab were not more likely to be in remission after 8 weeks of treatment compared with patients given placebo 32. Adverse events were few with daclizumab, with the most common being nausea in patients simultaneously treated with azathioprine31 as well as nasopharyngitis and fever 32…”
Section: Targeting the Adaptive Immune Systemmentioning
confidence: 99%
“…This effect was most prominent in patients with elevated baseline concentrations of CRP [36]. An additional phase 2 study of fontolizumab at lower subcutaneous doses of 1.0 mg/kg or 4.0 mg/kg in 196 patients with active CD did not demonstrate efficacy at day 28 [37]. These results indicate that a single dose may not be sufficient to achieve a significant improvement.…”
Section: Fontolizumab (Anti-interferon-γ Antibody)mentioning
confidence: 96%
“…In a little open-label study on 10 steroid-resistant UC patients, Daclizumab (administered in two infusions 4 weeks apart), permitted clinical remission in 80% and clinical response in 50% of patients. Contemporary decrease in CRP serum level and in CD25+ mucosal T cells number, while no effect on mucosal healing were observed [130].…”
Section: Inhibitors Of T Cells Proliferationmentioning
confidence: 96%